1996
DOI: 10.1037/0022-006x.64.2.391
|View full text |Cite
|
Sign up to set email alerts
|

The New Hampshire study of supported employment for people with severe mental illness.

Abstract: This study compared supported employment services in 2 contrasting programs: (a) Group Skills Training, a professional rehabilitation agency outside of the mental health center that provided pre-employment skills training and support in obtaining and maintaining jobs, or (b) the Individual Placement and Support (IPS) model, which integrated clinical and vocational services within the mental health center. People with severe mental disorders who expressed interest in competitive employment (N = 143) were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
290
3
8

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 315 publications
(311 citation statements)
references
References 25 publications
(44 reference statements)
10
290
3
8
Order By: Relevance
“…Those who obtain CE via IPS have been shown to have improved self-esteem, quality of life, social inclusion, and psychiatric symptoms [20,[31][32][33], and improvements have been shown to be maintained during follow-up, for as many as 12 yr [7,34]. Although IPS has been associated with improvements in some nonvocational outcomes in observational outcome studies, these improvements have not been greater than those demonstrated by other rehabilitation programs when evaluated in randomized trials [33,[35][36][37][38]. Several other studies that favored IPS with regard to vocational outcomes failed to find greater improvement in non-vocational outcomes [27,37].…”
Section: Supported Employmentmentioning
confidence: 98%
“…Those who obtain CE via IPS have been shown to have improved self-esteem, quality of life, social inclusion, and psychiatric symptoms [20,[31][32][33], and improvements have been shown to be maintained during follow-up, for as many as 12 yr [7,34]. Although IPS has been associated with improvements in some nonvocational outcomes in observational outcome studies, these improvements have not been greater than those demonstrated by other rehabilitation programs when evaluated in randomized trials [33,[35][36][37][38]. Several other studies that favored IPS with regard to vocational outcomes failed to find greater improvement in non-vocational outcomes [27,37].…”
Section: Supported Employmentmentioning
confidence: 98%
“…For example, in the area of work, a recovery goal for many consumers is competitive employment that is congruent with personal preferences and is personally satisfying. These three elements-competitive employment (Drake, McHugo, Becker, Anthony, & Clark, 1996), match with personal preferences (Becker, Drake, Farabaugh, & Bond, 1996), and job satisfaction )-have been operationally defined and measured, although this is not to say that other aspects of community integration in this domain do not warrant more psychometric work.…”
Section: Definition Of Community Integration and Its Relationship Tomentioning
confidence: 99%
“…Meanwhile, at the local level, experiments in the provision of services were occurring that had important effects on the ways that people with serious mental illness were being treated. Group homes (Okin 1983), Assertive Community Treatment Teams (Stein and Test 1980), Clubhouses (Sweet 1999), transitional employment services (Drake et al 1996), integrated treatment such as the Village in Long Beach (Chandler et al 1997), consumer-directed and -operated programs and other services of the consumer and survivor movements (Athena 2010;Tomes 2006), all had a major impact on the treatment landscape across America. An emphasis on person-centered care, rehabilitation and recovery, community integration, and experiments in the closure of state hospitals (Okin 1995) similar to Trieste's initiatives in many places supplanted the emphasis on mere symptom control.…”
Section: The San Francisco Mental Health Systemmentioning
confidence: 99%